A new construction for harmonic evolute surfaces of quasi tangent surfaces with quasi frame - Talat Körpınar; Gül Uğur Kaymanlı (Boletim da Sociedade Paranaense de Matemática, 2022)
In this paper, we study a harmonic evolute surface of quasi tangent surface associated with quasi frame. We construct quasi tangent surface with first and second fundamental forms. Moreover, we determine harmonic evolute surface of quasi tangent surface by using these fundamental forms. Finally, we obtain some new results about these new surfaces.